The use of β(2)-agonist therapy before hospital attendance for severe asthma exacerbations: a post-hoc analysis - Patel, Mitesh (NPJ Prim Care Respir Med, 2015)
BACKGROUND: Patterns of inhaled β(2)-agonist therapy use during severe asthma exacerbations before hospital attendance are poorly understood. AIMS: To assess β(2)-agonist use prior to hospital attendance. METHODS: We undertook an exploratory post hoc analysis of data from a 6-month clinical trial of 303 patients randomised to combination budesonide/formoterol inhaler according to a Single combination inhaler as Maintenance And Reliever Therapy regimen (‘SMART’) or fixed-dose budesonide/formoterol with salbutamol as reliever (‘Standard’). Patterns of β(2)-agonist use for 14 days before hospital attendance with a severe asthma exacerbation were determined by electronic monitoring of inhaler use. RESULTS: There were 22 hospital attendances in 16 patients during the study. Seven and nine hospital attendances were eligible for analysis in the SMART and Standard groups, respectively. In both regimens, β(2)-agonist use increased before hospital attendance, with a median (range) maximum daily number of actuations of 14 (9 to 63) budesonide/formoterol in SMART and 46 (6 to 95) salbutamol in Standard with 4 (0 to 10) budesonide/formoterol actuations on the day of maximal salbutamol use. There was delay in obtaining medical review despite high β(2)-agonist use, in 9/16 patients. Different patterns of use were observed, including repeated days of no inhaled corticosteroid despite marked salbutamol use, which occurred in 3/9 patients in the Standard group. CONCLUSIONS: Delay in obtaining medical review in association with high β(2)-agonist use is common in patients before hospital presentation with severe exacerbations of asthma. The SMART regimen reduced nonadherence with inhaled corticosteroid therapy during severe exacerbations.